Pengaruh Pelayanan Publik dan Lingkungan Kerja terhadap Kepuasan Karyawan PT. Samudera Agencies Indonesia - Ari Tolaba; Khamo Waruwu; Mella Yuita (Universitas 45 Surabaya, 2025)
This research aims to analyze the influence of Public Services and Work Environment on Employee Satisfaction at PT. Samudera Agencies Indonesia. The population in this study were employees of PT. Samudera Agencies Indonesia. The sampling technique used was a total sampling technique or saturated sample with a total of 30 respondents. Data collection techniques by distributing questionnaires. The analysis used is multiple regression analysis with t test and F test and coefficient of determination. The data processing tool used is SPSS version 24. The results of this research show that the Public Service variable (X1) has a significance value of 0.030 <0.05 so it can be concluded that the Public Service variable (X1) has a positive and significant effect on the Employee Satisfaction variable , as well as the Work Environment variable (X2) with a significance value of 0.032 <0.05 so it can be concluded that the Work Environment variable (X2) has a positive and significant effect on Employee Satisfaction at the PT Office. Samudera Agencies Indonesia. Simultaneously, the F test results with a significance value of 0.006 <0.05, so it can be concluded that the Public Service and Work Environment variables simultaneously have a positive and significant effect on Employee Satisfaction at the PT Office. Samudera Agencies Indonesia. The RSquare value of the independent variable is 31.8% in influencing the dependent variable Employee Satisfaction at the PT Office. Samudera Agencies Indonesia, while the rest is influenced by other factors outside this research.